Use of functional electrical stimulation associated with locomotor training in the improvement of gait speed in patients with incomplete spinal cord injury: a systematic review (Research, Society and Development, 2022)
Background: a spinal cord injury leads to loss of control over intact neuromuscular systems. Preliminary research suggests that combination of functional electrical stimulation (FES) with locomotor training could be used to improve functional mobility of patients with incomplete spinal cord injury (SCI). Purpose: to evaluate the methodological quality of clinical trials that used FES plus locomotor training to increase walking speed in patients with SCI. Methods: Systematic review conducted through a literature search in the databases MedLine/Pubmed, PEDro and Cochrane (June to November 2020) was conducted, using the following keywords: (i) electric stimulation therapy; (ii) spinal cord injury (iii) locomotor training; and (iv) walking speed. Methodological quality of individual studies was assessed using the PEDro scale. Results: 1139 studies were identified. Of these, four studies were included after eligibility criteria check. PEDro score ranged between 2 and 6. Conclusion: although studies suggests that combination of FES and locomotor training coulde be beneficial, further studies with better methodological rigor are needed. Best stimulation parameters for improving walking speed, when associated with locomotor training should be investigate.